Respostas

2014-07-16T11:16:21-03:00
1°) sabemos que nesta função temos: { (f(x)=ax+b  e f(-1)= 3 e f(1) = -1 .

se f(x)= ax+b  ∈  f(-1)=4 , onde : {  x=-1  e  f(x)=3 
               a*(-1)+b=3
               -a + b = 3  primeira equação

2°) se f(x)= ax+b  ∈ f(1)= -1 , onde : {  x=1  e f(x)= -1
                a*1+b=-1
                 a+b=-1 segunda equação 

3°) resolva o sistema das equações.
             {-a+b=3
               a+b=-1  logo, temos  a=-2    e   b= 1    resposta   -2 e 1  letra A



1 1 1